Induction of the Orthogonal Smectic A Phase in Mixtures of Nematic Tolanes with Positive and Negative Dielectric Anisotropy - Paulina Zieja; Barbara Klucznik; Marzena Tykarska (Biuletyn Wojskowej Akademii Technicznej, 2022)
Induction of the orthogonal smectic A phase occurs in mixtures of nematic compounds with positive and negative dielectric anisotropy. The aim of this work is to determine influence of a molecular structure of compounds on the induction strength of this phase. Cyclohexyl tolanes with the terminal group ‒OCF3, differing with a lateral substitution of a rigid core with fluorine atoms, were mixed with tolanes with two fluorine atoms in a lateral position and different lengths of a terminal alkoxy chain. Based on phase diagrams, obtained with the use of a polarising optical microscope, the influence of a structure of both types of compounds on the induction of the SmA phase is presented. Both, an increase in a number of fluorine atoms in a rigid core and a decrease in an alkoxy chain length cause a decrease in the strength of the SmA phase induction in the investigated systems.Keywords: chemistry, liquid crystals, smectic A phase induction, miscibility studies